PERFORMANCE ANALYSIS OF SURGE CURRENT PROTECTION USING SUPERCONDUCTORS - K. Makinde; F. O Enemuoh; O.K Lawal; I Umar; B Abubakar; M.K Mahmood (European Scientific Journal, ESJ, 2014)
Increase in power generation capacity of electrical power systems has lead to increase in the fault current level which can exceed the maximum designed short-circuit ratings of the switchgear. Many conventional protective devices installed for protection of excessive fault current in electric power systems, especially at the power stations are the circuit breakers, tripped by over-current protection relay. They have the responsetime delay that allows initial of two or three fault current cycles to pass through before getting activated. Superconducting Fault Current Limiter (SFCL) is innovative electric equipment which has the capability to reduce fault current level within the first cycle of fault current. The application of the fault current limiter (FCL) would not only decrease the stress on network devices, but also can offer a connection to improve the reliability of the power system. There are various types of FCLs, which are made of different superconducting materials and have different designs. They are categorized into three broad types: the resistive type, the inductive type and bridge type SFCL. We discussed the operating characteristics of SFCL introduced into a simplified power transmission model system. It was finally revealed that SFCL could satisfactorily bring about the functions of fault current suppression and power system stability improvement. In this report, results of investigations carried out to assess the effectiveness of the options available for fault level management as well as, where necessary, their impact on voltage profiles and system stability are presented and discussed. In this paper, Powerworld simulator was used in running a resistive type of SFCL.